Functional Characterization of CLCN4 Variants Associated With X-Linked Intellectual Disability and Epilepsy - Guzman, Raul E.; Sierra-Marquez, Juan; Bungert-Plümke, Stefanie; Franzen, Arne; Fahlke, Christoph (Frontiers in Molecular Neuroscience, 2022)
Early/late endosomes, recycling endosomes, and lysosomes together form the endo-lysosomal recycling pathway. This system plays a crucial role in cell differentiation and survival, and dysregulation of the endo-lysosomal system appears to be important in the pathogenesis of neurodevelopmental and neurodegenerative diseases. Each endo-lysosomal compartment fulfills a specific function, which is supported by ion transporters and channels that modify ion concentrations and electrical gradients across endo-lysosomal membranes. CLC-type Cl-/H+ exchangers are a group of endo-lysosomal transporters that are assumed to regulate luminal acidification and chloride concentration in multiple endosomal compartments. Heterodimers of ClC-3 and ClC-4 localize to various internal membranes, from the endoplasmic reticulum and Golgi to recycling endosomes and late endosomes/lysosomes. The importance of ClC-4-mediated ion transport is illustrated by the association of naturally occurring ClCN4 mutations with epileptic encephalopathy, intellectual disability, and behavioral disorders in human patients. However, how these mutations affect the expression, subcellular localization, and function of ClC-4 is insufficiently understood. We performed a functional analysis of 12 ClCN4 variants associated with X-linked intellectual disability and epilepsy using heterologous expression in mammalian cells, biochemistry, confocal imaging, and whole-cell patch clamp recordings. The mutations led to a variety of changes in ClC-4 function, ranging from gain/loss of function and impaired heterodimerization with ClC-3 to subtle impairments in transport functions. Our results demonstrate that even slight functional changes to the endosomal Cl-/H+ exchangers can cause serious neurological symptoms.